EASE Guidelines for Authors and Translators of Scientific Articles to be Published in English - journal "Morphologia, Editorial office (Морфологія / Morphologia / Morfologìâ, 2011)
In order to increase the effectiveness of international scientific collaboration, articles and other scientific publications should be FULL, LACTONY and RELEVANT. These general guidelines are intended to help authors, translators and editors to achieve this goal.